(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Contemporary marketing thoughts seem too rigidly glued to the view that consumer purchase decision-making processes are primarily motivated by extrinsic variables and rational drivers more than anything else. However, neuroscientific evidence from archived and current sources shows that intrinsic brain processes activated by subtle sensory cues significantly influence consumer purchase decisions. Exploring that illuminating discourse, this study employs a meta-analytical approach, systematically searching databases such as Scopus and Web of Science to synthesize existing literature to bring out insights that enrich our understanding of consumer behaviour. The analysis culminates in the conceptualisation of a five-construct neurological model that embody the sequential consumer decision-making process as comprised of: the challenge, inquiry, experiment, experience, and content. Rigorous inclusion-exclusion criteria narrowed an initial pool of 457 articles to 98 relevant studies, assessing sample sizes, demographic characteristics, and effect sizes. The DerSimonian-Laird random-effects model evaluated between-study variance, supplemented by sensitivity and stratified analyses to refine insights. Key takeaways from the model highlight the importance of addressing intrinsic consumer needs during the neural challenge stage, delivering clear information during neural inquiry, and enhancing brand loyalty through experiential learning in neural experimentation. This theoretical framework enriches our understanding of the interplay between emotion and rationality, offering practical implications for marketing strategies and encouraging insights into evolving consumer psychology.